2021
DOI: 10.1177/10538259211001568
|View full text |Cite
|
Sign up to set email alerts
|

Nature Connection and 360-Degree Video: An Exploratory Study With Immersive Technology

Abstract: Background: Immersive technologies may be an avenue to explore the construct of human–nature connection more thoroughly and without some of the obstacles to accessing nature in-person. Purpose: The aim of this project was to discover if self-exposure to immersive virtual nature can lead to any change in nature connectedness. Methodology/Approach: Participants were recruited from the Texas State University campus and randomized into three experimental conditions: a filmed library or nature experience, and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Two studies reported a relationship and independence with nature after walking in a virtual forest [54,60]. Sneed et al [54] conducted a study using videos captured while walking in a real environment for 10 min.…”
Section: Other Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported a relationship and independence with nature after walking in a virtual forest [54,60]. Sneed et al [54] conducted a study using videos captured while walking in a real environment for 10 min.…”
Section: Other Effectsmentioning
confidence: 99%
“…Two studies reported a relationship and independence with nature after walking in a virtual forest [54,60]. Sneed et al [54] conducted a study using videos captured while walking in a real environment for 10 min. Consequently, the Nature Relatedness Scale (NRS) was increased in the group that walked through the real and virtual forests, but the group that observed a virtual library experienced little change.…”
Section: Other Effectsmentioning
confidence: 99%
“…Outdoor recreation professionals have largely not been involved in creating virtual reality content or recruiting participants through this pathway. While there are numerous studies showing its potential with research populations (e.g., Browning et al, 2020;Sneed et al, 2021), nature in virtual reality applications does not have the presence and popularity of video games and other computer-generated content. Future research should focus on the potential for 360-degree video experiences and how these experiences can be made more widely available.…”
Section: Discussion and Potential Significancementioning
confidence: 99%
“…Virtual reality provides a potential pathway to motivate students to pursue realworld outdoor recreation. Experiences with virtual nature may increase nature connectedness (Sneed et al, 2021), but it is less clear whether these experiences encourage intent to recreate outside. The purpose of this study was to investigate whether virtual reality nature experiences influence intent and self-efficacy to recreate in nature among college students.…”
mentioning
confidence: 99%
“…(i.e., score equal to 6.5) percentiles, we categorized the studies into "high quality", "medium quality" and "low quality" (Table S3). Fourteen studies were classified as having a high quality (Annerstedt et al, 2013;Blum et al, 2019;Browning, Mimnaugh et al, 2020;Hedblom et al, 2019;Huang et al, 2020;Lakhani et al, 2020;O'meara et al, 2020;Palanica et al, 2019;Rockstroh et al, 2019;Schutte et al, 2017;Sneed et al, 2021;Tabrizian et al, 2018;Wang et al, 2020;Yeo et al, 2020),a further sixteen studies (Anderson et al, 2017;Calogiuri et al, 2018;Chirico, & Gaggioli, 2019;Fleury et al, 2021;Hofman et al, 2021;Lindquist et al, 2020;Liszio, & Masuch, 2019;Liszio et al, 2018;Mattila et al, 2020;Reese et al, 2021;Schebella et al, 2020;Wang et al, 2019;Xiang et al, 2021;Yu et al, 2018;Yu et al, 2020) were classified as having "medium quality", and eight (Burmeister et al, 2018;Evensen et al, 2021;Gao et al, 2019a;2019b;Je, & Lee, 2020;Mostajeran et al, 2021;Pals et al, 2014;van Vliet et al, 2021) as having "low quality". The item in which we found a lower overall score is that on power analysis (pre-or post-hoc) which...…”
Section: Quality Assessmentmentioning
confidence: 99%